Poor cervical proprioception as a risk factor for concussion in professional male rugby union players. (May 2022) - Farley, T.; Barry, E.; Bester, K.; Barbero, A.; Thoroughgood, J.; De Medici, A.; Sylvester, R.; Wilson, M.G.
Abstract: Background: Concussion is one of the most common injuries in male professional Rugby Union ('rugby') and accounts for significant time loss from training and competition. Despite the most recent Concussion in Sport Group consensus statement recommending a focus on the identification of modifiable risk factors, limited evidence for their existence is available. Objective: To investigate the association between cervical proprioception and concussion incidence in a group of professional male rugby players over the course of a full season. Methods: 165 players were assessed at pre-, mid- and end of season time points using the Cervical Joint Position Error Test (CJPET). Associations with diagnosed concussion injuries are presented as incidence rate ratios with 95% confidence intervals. We present the Incidence Rate Ratios (IRR) for a 10% increase in each variable and compared results against concussion using match minutes to account for risk exposure. Results: During the study period, 45 concussions were incurred by 44 players [or 19.7 concussions per 1000 player-match hours]. There was a significant association between right rotation repositioning error and concussion, with a 5% increase in concussion rate for each 10% increase in gross right rotation error (P = 0.021). Conclusion: Poor gross right rotation repositioning error is a modifiable intrinsic risk factor for concussion in professional male rugby players. Interventions to improve proprioceptive function may act as an effective method for reducing concussion incidence in this population. Highlights: Poor cervical proprioception is positively correlated with concussion incidence. Concussion rate increases by 5% for a 10% increase in gross right rotation error. Rate increases by 6% for each 10% increase in horizontal right rotation error. Left rotation and extension repositioning error significantly improve over a season. Gross right rotation repositioning error does not change over a rugby season.